TƯƠNG QUAN XÓI LỞ - BỒI TỤ MỘT SỐ KHU VỰC LÒNG SÔNG TIỀN, SÔNG HẬU - Hải, Hà Quang (Vietnam Journal of Earth Sciences, 2011)
Correlation of erosion - aggradation in areas along Tien and Hau Rivers Riverside erosion, one of the most severe natural disasters, has been occuring along the banks of Tien river and Hau for many years. Many segments in Tan Chau, Hong Ngu, Sa Dec,… are seriously affected by the disaster. There are numbers of studies that have indentified levels, causes of the erosion process and proposed solutions for the decrease of erosional negative influences. Based on analysing satellite images, map, monitoring a series of channel cross - sections by echosounder and the study of geomorphology, the study concluded that erosion and deposition, specific natural processes of braided and meandering river in flood plains, balance one another. Bulding stone jetties and uncomprehensive management have accelerated both two processes: erosion and deposition. Combining the dredge river bed and exploitation of materials for construction is the most effective solution to reduce river shore erosion.